Fat Graft Enhanced With Adipose-Derived Stem Cells in Aesthetic Breast Augmentation: Clinical, Histological, and Instrumental Evaluation. (22nd October 2019) - Gentile, Pietro; Kothari, Ashutosh; Casella, Donato; Calabrese, Claudio
Abstract: Background: Fat graft enhanced with adipose-derived stem cells (FG-e-ASCs) has been utilized in outcomes of radiotherapy after mastectomy, breast soft tissue defects, ulcers, and loss of substance. The authors present their experience utilizing FG-e-ASCs in breast augmentation. Objectives: The aim of this study was to evaluate the safety and efficacy of a study group (SG) regarding utilization of FG-e-ASCs in breast augmentation for aesthetic improvement, comparing the results with a control group (CG). Methods: A total of 46 patients affected by breast hypoplasia were treated with FG-e-ASCs, comparing results with those of a CG (n = 30) treated with fat graft not enhanced with adipose-derived stem cells (FG-ne-ASCs). The preoperative evaluation included a complete clinical evaluation, a photographic assessment, magnetic resonance imaging of the soft tissue, ultrasound, and mammography. Postoperative follow-up took place at 1, 3, 7, 12, 24, and 48 weeks and then annually. Results: The patients treated with FG-e-ASCs showed 58% maintenance of the contour restoring and of 3-dimensional (3D) volume after 3 years compared with the patients of the CG treated with FG-ne-ASCs, who showed 29% maintenance. In 67.4% (n = 31) of breast augmentations treated with FG-e-ASCs, we observed a restoration of the breast contour and an increase of 10.3 mm in the 3D volume after 36 months, which was observed in only 20.0% (n = 6) of patients in the CG treated with FG-ne-ASCs. Volumetric persistence in the SG was higher than that in the CG ( P  < 0.0001 SG vs CG). Conclusions: Utilization of FG-e-ASCs was safe and effective in this series of cases performed. Level of Evidence: 4: